INVESTIGATING STUDENTS’ EXPERIENCES WITH ONLINE ASSESSMENTS: THE USE OF QUIZIZZ IN ESP COURSE - Made Anggi Arlina Putri, Ni (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Gamified quiz software is increasingly popular in English for Specific Purposes (ESP) instruction due to its ability to enhance student engagement and motivation. However, the effectiveness and user experience of gamified tools like Quizizz in ESP contexts remain underexplored. This study explores students' experiences with Quizizz in an ESP class, focusing on its advantages, ease of use, and challenges. Using a quantitative survey design, data were gathered from 77 Physics Education students through a Likert-scale questionnaire distributed online at the end of the 2024/2025 Odd Semester and analyzed descriptively. The results show that 86.9% of students agreed or strongly agreed that gamification features increased their motivation, and 73.3% felt more confident answering questions after using Quizizz. Its user-friendly interface and accessibility also facilitate participation. However, challenges such as time limits, unstable internet connections, and technical difficulties affected their experience. Some students felt pressured by timed quizzes, while poor network stability hindered their participation. These findings highlight both the pedagogical benefits and limitations of gamified assessments in ESP learning. To enhance pedagogical value, the study recommends adjusting quiz timing, improving technical infrastructure, and tailoring gamification to reduce anxiety while sustaining engagement. Further research should examine the long-term effects of gamified testing on ESP learning outcomes in various instructional contexts. ABSTRAK Perangkat lunak kuis gamifikasi semakin populer dalam pengajaran Bahasa Inggris untuk Tujuan Tertentu (ESP) karena kemampuannya untuk meningkatkan keterlibatan dan motivasi siswa. Namun, efektivitas dan pengalaman pengguna alat gamifikasi seperti Quizizz dalam konteks ESP masih kurang dieksplorasi. Studi ini mengeksplorasi pengalaman siswa dengan Quizizz di kelas ESP, dengan fokus pada keuntungan, kemudahan penggunaan, dan tantangannya. Menggunakan desain survei kuantitatif, data dikumpulkan dari 77 mahasiswa Pendidikan Fisika melalui kuesioner skala Likert yang didistribusikan secara daring pada akhir Semester Ganjil 2024/2025 dan dianalisis secara deskriptif. Hasilnya menunjukkan bahwa 86,9% siswa setuju atau sangat setuju bahwa fitur gamifikasi meningkatkan motivasi mereka, dan 73,3% merasa lebih percaya diri menjawab pertanyaan setelah menggunakan Quizizz. Antarmuka yang ramah pengguna dan aksesibilitasnya juga memfasilitasi partisipasi. Namun, tantangan seperti batas waktu, koneksi internet yang tidak stabil, dan kesulitan teknis memengaruhi pengalaman mereka. Beberapa siswa merasa tertekan oleh kuis berbatas waktu, sementara stabilitas jaringan yang buruk menghambat partisipasi mereka. Temuan ini menyoroti manfaat pedagogis sekaligus keterbatasan penilaian gamifikasi dalam pembelajaran ESP. Untuk meningkatkan nilai pedagogis, studi ini merekomendasikan penyesuaian waktu kuis, peningkatan infrastruktur teknis, dan penyesuaian gamifikasi untuk mengurangi kecemasan sekaligus mempertahankan keterlibatan. Penelitian lebih lanjut perlu mengkaji efek jangka panjang dari pengujian gamifikasi terhadap hasil pembelajaran ESP dalam berbagai konteks pembelajaran.